Gold investment : how far economic factor affect total volume of gold investment in Kuwait Finance House (M) Berhad - Nur Badriyah, Mokhtar (2018)
The aim of this research paper is to determine the impact of economic variables towards gold investment account in Kuwait Finance House (M) Berhad over the period of 2010 to 2016. This research tests the relationship between gold price, employment, inflation and gold investment account. In this research applied the Regression (Ordinary Least Square, OLS) to examine the impact of economic variables on gold investment account. The findings show that gold price, employment and inflation have significant impact towards gold investment account.